2017
DOI: 10.1167/iovs.16-20077
|View full text |Cite
|
Sign up to set email alerts
|

Sex Disparity in Survival of Patients With Uveal Melanoma: Better Survival Rates in Women Than in Men in South Korea

Abstract: Women with uveal melanoma have better survival probabilities relative to men with uveal melanoma. Our findings show a comprehensive picture of survival probability in uveal melanoma cancer patients in Korea, which requires further investigation of mechanism of the sex disparity in uveal melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…A recent study in 344 South Korean UM patients reported higher survival probabilities in females. 36 Several explanations can be proposed for the observed association of male gender with poor survival in our study, which was evident in the total cohort, as well as after 5 years of follow-up, in our competing risks regression analysis. One possibility is that males have larger and more advanced primary tumors than females, as described in some but not all reports.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…A recent study in 344 South Korean UM patients reported higher survival probabilities in females. 36 Several explanations can be proposed for the observed association of male gender with poor survival in our study, which was evident in the total cohort, as well as after 5 years of follow-up, in our competing risks regression analysis. One possibility is that males have larger and more advanced primary tumors than females, as described in some but not all reports.…”
Section: Discussionmentioning
confidence: 51%
“…A recent study in 344 South Korean UM patients reported higher survival probabilities in females. 36 …”
Section: Discussionmentioning
confidence: 99%
“…26 27 Others showed consistent results. 28 The high SIR of diagnosing patients in FiPUM group can be an indicator of the physicians' concern about the metastasis of UM to other sites and their meticulous examination of patients thereafter. While examining the fundus of is not indicated in most of the guidelines of the malignancies elsewhere in the body resulting in failure to find early UM.…”
Section: Discussionmentioning
confidence: 99%
“… 21 , 23 The pattern is however not apparent in the articles by Zloto et al 2013 and Park et al 2017. 16 , 17 Park et al reported a relatively short mean follow‐up of 5.4 years. Zloto et al described a two‐fold excess of male melanoma‐related mortality in the first 10 years after diagnosis but did not report median follow‐up for survivors or how many of their patients remained in their data after the first decade.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 14 , 15 Male sex has also been identified as an independent predictor of metastasis and UM‐related death within the first decade after diagnosis. 16 , 17 , 18 , 19 Notably, other large randomized studies or retrospective cohort studies with longer follow‐up have failed to identify sex‐based differences in survival rates. 20 , 21 , 22 , 23 Some observations even indicate that young women have a relatively worse prognosis than young men.…”
Section: Introductionmentioning
confidence: 99%